Domination type parameters of Pell graphs - Özer, Arda Bugra (Ars mathematica contemporanea, 2023)
Pell graphs are defined on certain ternary strings as special subgraphs of Fibonacci cubes of odd index. In this work the domination number, total domination number, 2- packing number, connected domination number, paired domination number, and signed domination number of Pell graphs are studied. Using integer linear programming, exact values and some estimates for these numbers of small Pell graphs are obtained. Furthermore, some theoretical bounds are obtained for the domination numbers and total domination numbers of Pell graphs.
Keywords: celoštevilsko linearno programiranje; dominacijsko število; domination number; Fibonacci cube; Fibonaccijeva kocka; integer linear programming; Pell graphs; Pellovi grafi